Sintesis Mikroemulsi Menggunakan Surfaktan dan Minyak Atsiri Kulit Buah Lemon (Citrus limon) Sebagai Face Mist - Suciati, Tania; Suhendra, Lutfi; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2023)
This study aims to determine the effect of the ratio of the mixture of surfactants and essential oil of lemon rind (Citrus limon) and determine the ratio of surfactant and essential oil of lemon rind (Citrus limon) to obtain the best microemulsion characteristics. This experiment used a completely randomized design with step 1 ratio of surfactant mixture (Tween 20: Tween 80: Span 80) which was 97: 2.75: 0.25; 97:2.5:0.5; 97:2.25:0.75; 97:2.0:1; 97:1.75; 1.25. Then, in step 2 the ratio of surfactant and lemon peel essential oil was 90:10; 87.5: 12.5; 85:15; 82.5:17.5; 80:20. Data were analyzed using analysis of variance using excel. The results showed that the ratio of the mixture of surfactants and lemon peel essential oil had an effect on the characteristics of the resulting microemulsion. The ratio of surfactant mixture 97: 2.75: 0.25 (Tween 20: Tween 80: Span 80) was the best treatment for making lemon peel essential oil microemulsion with the lowest turbidity values ??before and after centrifugation, namely 0.245±0.010% and 0.203±0.059 %. The ratio of surfactant and essential oil of lemon peel 85:15 was the best treatment with turbidity index values ??before and after centrifugation 0.298±0.037% and 0.334±0.161%, respectively. Lemon peel essential oil microemulsion has a particle size of 1272.2 nm and a potential zeta value of 0 mV. Lemon peel essential oil microemulsion 85:15 was stable for 8 weeks of storage.